Wunderlich Syndrome: An Unusual Cause of Abdominal Pain with Hypovolaemia. Issue 6 (November 2013) - Chan, KP
Wunderlich syndrome, or spontaneous retroperitoneal haemorrhage, is a rare but potentially fatal condition. I report a case of a middle-aged lady who presented with this rare condition where a bedside point-of-care ultrasound scan expedited the management of the patient. (Hong Kong j.emerg.med. 2013;20:385-388)